1997
DOI: 10.1021/es960880a
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of Vitamin B12 by Shewanella alga Strain BrY with Subsequent Transformation of Carbon Tetrachloride

Abstract: The ability of a metal-reducing bacterium to microbially reduce vitamin B12 was determined to expand our understanding of the role vitamin B12 plays in the transformation of halogenated compounds in microbial systems. The subsequent transformation of chlorinated methanes catalyzed by this microbially-reduced vitamin B12 was then evaluated. When incubated in the presence of Shewanella alga strain BrY and an electron donor, the microbial reduction of vitamin B12a to B12r was observed as a shift in the vitamin B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The results taken as a whole from this study, indicate that reductive hydrogenolysis was a minor pathway; whereas substitutive reactions was the major pathway in cobalamin supplemented cultures. To support this hypothesis, the chemical reaction of biologically reduced CNB12 with CT resulted in CO as the major product (92%); whereas CF was a minor product (1.4%) (Workman et al 1997). In active methanogenic consortia CO would be further converted to CH 4 , acetate and CO 2 (Sipma et al 2003).…”
Section: Role Of Redox Active Vitamins On Biotransformation Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results taken as a whole from this study, indicate that reductive hydrogenolysis was a minor pathway; whereas substitutive reactions was the major pathway in cobalamin supplemented cultures. To support this hypothesis, the chemical reaction of biologically reduced CNB12 with CT resulted in CO as the major product (92%); whereas CF was a minor product (1.4%) (Workman et al 1997). In active methanogenic consortia CO would be further converted to CH 4 , acetate and CO 2 (Sipma et al 2003).…”
Section: Role Of Redox Active Vitamins On Biotransformation Productsmentioning
confidence: 99%
“…Oxidized cobalamins occur in the Co(III) state and can be reduced to the Co(II) and Co(I) states with standard reduction potentials at pH 7 (E 00 ) versus the standard hydrogen electrode (SHE) of 0.20 and À0.61 V for the couples Co(III)/Co(II) and Co(II)/Co(I), respectively (Lexa & Saveant 1983). The iron reducing bacterium, Shewanella alga strain BrY was shown to reduce cobalamin Co(III) to cobalamin Co(II) when provided with an adequate electron donor such as lactate or H 2 (Workman et al 1997). Similarly the reduction was also catalyzed by Salmonella enterica strain serovar Typhimurium LT2.…”
Section: Cobalamins As Redox Mediators During Ct-bioconversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized cobalamins occur in the Co(III) state and can potentially be reduced to the Co(II) and Co(I) states with standard reduction potentials at pH 7 (E¢ 0 ) versus the standard hydrogen electrode (SHE) of 0.20 and )0.61 V for the couples Co(III)/ Co(II) and Co(II)/Co(I), respectively (Lexa & Saveant 1983). The iron reducing bacterium, Shewanella alga strain BrY was shown to reduce cobalamin Co(III) to cobalamin Co(II) when provided with an adequate electron donor such as lactate or H 2 (Workman et al 1997). Similarly the reduction was also catalyzed by Salmonella enterica strain serovar Typhimurium LT2.…”
Section: Introductionmentioning
confidence: 99%
“…-Workman et al [155] studied CT dechlorination by an iron-reducing microbial culture amended with vitamin B 12 . They found that the culture reduced cobalt(III) in vitamin B 12 to cobalt(II), and that the reduced vitamin B 12 carried out CT dechlorination.…”
Section: Carbon Tetrachloridementioning
confidence: 99%